Bezpečnost pro 90. léta (Czech Journal of International Relations, 1995)
Security studies for the 1990s. Ed. by Richard Shultz, Roy Godson, Ted Greenwood.McLean (USA),Brassey's 1993, 423 stran, ISBN 0-02-881072-4.